Comparison of behavioral intervention and sensory integration therapy on challenging behavior of children with autism. (18th August 2017) - Lydon, Helena; Healy, Olive; Grey, Ian
Abstract : The current study used an AB crossover design to directly compare the effects of sensory integration therapy (SIT) and behavioral intervention (BI) on the challenging behavior of 10 participants with autism spectrum disorder. During the intervention phase, all participants received both treatments. Follow‐up probes were conducted 1 month following intervention for 4 participants implementing the more effective intervention. The results showed that BI successfully reduced challenging behavior to low‐ or near‐zero levels. In contrast, SIT resulted in higher and more variable rates of challenging behavior. One exception was noted for Participant 4 who engaged in a decreased level of challenging behavior during SIT. The findings are discussed in relation to implication for practice and future research.